CRIMINAL RESPONSIBILITY FOR PERPETRATORS OF HACKING CRIMINAL ACTS - Lunggana, Guruh Tirta; Rahmat, Diding; Asri, Ardison (JILPR Journal Indonesia Law and Policy Review, 2026)
Hacking is a form of cybercrime that threatens the security of electronic systems and personal data. In Indonesia, this act is strictly regulated in Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE Law), as amended by Law No. 19 of 2016. Article 30 of the ITE Law prohibits anyone from accessing electronic systems without authorization, whether to obtain information or by breaching security systems. Criminal liability for hacking is emphasized in Article 46 of the ITE Law, with significant penalties of imprisonment and fines. This study shows that the criminal elements in hacking include unlawful acts, malicious intent (mens rea), and the consequences caused. Legally, this regulation reflects the state's commitment to protecting the integrity and privacy of electronic systems. However, its imple-mentation requires support from competent law enforcement agencies and regulations that are adaptive to technological developments. Therefore, efforts to enhance capacity, update laws, and educate the public are needed to create a legal system capable of effectively responding to cybercrime.